PHANGS-JWST first results: rapid evolution of star formation in the central molecular gas ring of NGC 1365 - Schinnerer, Eva; Emsellem, Eric; Henshaw, Jonathan D.; Liu, Daizhong; Meidt, Sharon E.; Querejeta, Miguel; Renaud, Florent; Sormani, Mattia C.; Sun, Jiayi; Egorov, Oleg; Larson, Kirsten L.; Leroy, Adam K.; et al. (The astrophysical journal. Part 2, Letters, 2023)
Large-scale bars can fuel galaxy centers with molecular gas, often leading to the development of dense ringlike structures where intense star formation occurs, forming a very different environment compared to galactic disks. We pair ∼0.″3 (30 pc) resolution new JWST/MIRI imaging with archival ALMA CO(2-1) mapping of the central ∼5 kpc of the nearby barred spiral galaxy NGC 1365 to investigate the physical mechanisms responsible for this extreme star formation. The molecular gas morphology is resolved into two well-known bright bar lanes that surround a smooth dynamically cold gas disk (R gal ∼ 475 pc) reminiscent of non-star-forming disks in early-type galaxies and likely fed by gas inflow triggered by stellar feedback in the lanes. The lanes host a large number of JWST-identified massive young star clusters. We find some evidence for temporal star formation evolution along the ring. The complex kinematics in the gas lanes reveal strong streaming motions and may be consistent with convergence of gas streamlines expected there. Indeed, the extreme line widths are found to be the result of inter-“cloud” motion between gas peaks; ScousePy decomposition reveals multiple components with line widths of 〈σ CO,scouse〉 ≈ 19 km s−1 and surface densities of , similar to the properties observed throughout the rest of the central molecular gas structure. Tailored hydrodynamical simulations exhibit many of the observed properties and imply that the observed structures are transient and highly time-variable. From our study of NGC 1365, we conclude that it is predominantly the high gas inflow triggered by the bar that is setting the star formation in its CMZ.
Gesehen am 17.04.2023